NIMG-45. DISTINGUISHING PROGRESSION FROM PSEUDOPROGRESSION IN GLIOBLASTOMA: COMBINED USE OF 18F-FLUCICLOVINE PET AND MULTI-PARAMETRIC MRI. (14th November 2022) - Nabavizadeh, Ali; Bagley, Stephen; Ware, Jeffrey B; Doot, Robert K; Young, Anthony; Ghodasara, Satyam; Zhao, Chao; Anderson, Hannah; Schubert, Erin; Carpenter, Erica L; Till, Jacob; Henderson, Fraser; et al.
Abstract: PURPOSE: Differentiation of tumor progression (TP) from pseudoprogression (PsP) is a major unmet need in post-treatment glioblastoma (GBM). 18 F-Fluciclovine is a synthetic amino acid PET radiotracer with higher uptake in tumor tissue vs. areas of treatment-related change. We investigated the value of 18 F-Fluciclovine PET for differentiating PsP from TP independent from and in combination with multi-parametric MRI. METHODS: We prospectively enrolled 30 patients with GBM with a new or enlarging contrast-enhancing lesion on MRI after chemoradiotherapy who were planned for surgical resection of the lesion. Patients underwent pre-operative 18 F-Fluciclovine PET and multi-parametric MRI. Following surgery, the relative percentages of viable tumor and therapy-related changes observed in histopathology were quantified. Patients were categorized as TP if viable tumor represented ≥ 50% of the specimen, mixed TP if < 50% and > 10%, and PsP if ≤ 10%. RESULTS: 18 patients had TP, 4 had mixed TP, and 8 PsP. Patients with TP/mixed TP had a significantly higher 40-50 minutes SUVmax (6.64 + 1.88 vs 4.11± 1.52, p=0.009) and an SUVmax cut-off of 4.66 provided 90% sensitivity and 83% specificity for differentiation of TP/mixed TP from PsP (AUC=0.856). A maximum cerebral blood volume (CBVmax) cut-off of 3.67 provided 90% sensitivity and 71% specificity for differentiation of TP/mixed TP from PsP (AUC=0.779). Combining a 40-50 minutes SUVmax cut-off of 4.662 and a relative CBVmax cut-off of 3.67 provided 100% sensitivity and 80% specificity for differentiating TP/mixed TP from PsP (AUC=0.95). The time activity curve patterns and time to peaks were not different between the groups. Normalization of PET parameters to normal brain parenchyma were not helpful to differentiate the groups due to variability in radiotracer uptake in normal brain between subjects. CONCLUSION: 18 F-Fluciclovine PET uptake can accurately differentiate PsP from TP in GBM patients, with even more accurate differentiation achieved when combined with MRI.